2005
DOI: 10.4049/jimmunol.174.9.5375
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Receptor (BCR) Cross-Talk: IL-4 Creates an Alternate Pathway for BCR-Induced ERK Activation That Is Phosphatidylinositol 3-Kinase Independent

Abstract: IL-4 has pleiotropic effects on B cells. These effects include alteration of subsequent BCR-triggered responses. To identify a molecular basis for this receptor cross-talk, we examined ERK activation and NF-κB induction. We found that treatment with IL-4, but not other cytokines, affected subsequent BCR signaling by creating a new pathway in which the need for PI3K in ERK activation was eliminated. In contrast, the need for PI3K in NF-κB induction was not altered. The new pathway for ERK required time to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 55 publications
7
29
0
Order By: Relevance
“…Similarly, stimulation of B cells with sCD40L, IL-4, and LPS reprograms the BCR signaling pathway, enhancing ERK activation and bypassing the requirement for phosphatidylinositol 3-kinase (PI3-K) [82][83][84][85][86]. The findings that only B cells chronically exposed to self-antigen are susceptible to repression by IL-6 and sCD40L suggests that chronic BCR-derived signals "reprogram" the outcome of IL-6R and CD40 signal transduction.…”
Section: A Short History Of Smmentioning
confidence: 93%
“…Similarly, stimulation of B cells with sCD40L, IL-4, and LPS reprograms the BCR signaling pathway, enhancing ERK activation and bypassing the requirement for phosphatidylinositol 3-kinase (PI3-K) [82][83][84][85][86]. The findings that only B cells chronically exposed to self-antigen are susceptible to repression by IL-6 and sCD40L suggests that chronic BCR-derived signals "reprogram" the outcome of IL-6R and CD40 signal transduction.…”
Section: A Short History Of Smmentioning
confidence: 93%
“…We investigated the possibility that bacterial products such as LPS might create an alternate BCR signaling pathway for MAPK activation similar to the alternate BCR signaling pathways established by B cell exposure to IL-4 and CD40L (2)(3)(4)(5). To evaluate this possibility, purified primary splenic B cells from normal BALB/c mice were treated with LPS for 24 h, washed, incubated in medium for 3 h ("rested"), and stimulated then with anti-Ig (15 g/ml) after which whole cell extracts were prepared and examined by Western blotting using ERK-specific and phospho-ERK (pERK)-specific Abs.…”
Section: Bcr-induced Erk Phosphorylation Becomes Resistant To Ly29400mentioning
confidence: 99%
“…However, recent evidence indicates that following exposure to CD40L or IL-4, alternate pathways for BCR signaling are established in which downstream events take place without the need for PI3K and other signalosome members through a process of receptor cross-talk (2)(3)(4)(5). Thus, the generally accepted need for signalosome elements in BCR signaling may simply represent an initial condition applicable only to naive cells, and not to B cells in the midst of an immune response.…”
mentioning
confidence: 99%
“…29,30 CLL cells exhibit glycosylation and folding defects of the IgM and CD79a chains, 31 which results in impaired BCR assembly and reduced sIgM in CLL samples. Our recent studies [32][33][34] have shown that IL-4 reprograms sIgM expression and substantially enhances anti-Ig-initiated B-cell activation in mouse B cells. In the present study, we find that CLL cells express a low level of total CD79b protein.…”
Section: Introductionmentioning
confidence: 99%